Makna Kultural Mitos dalam Budaya Masyarakat Banten - Ayatullah Humaeni (Antropologi Indonesia, 2012)
This article discusses various myths spread in several areas of Banten. How Bantenese society understands and believes in myths that have spread and are still maintained from generations to generations and how the roles and functions of myths for Bantenese society constitute the main focus of this article. This article is field research using ethnographical methods based on in anthropological perspective. To analyze the data, the researcher uses a structural-functional approach. Library research, participant-observation, and depth-interview are methods used to collect the data. Myth is a part of folklore that appear in almost every culture of the world, especially in traditional or pre-literate cultures. Various researches, especially conducted by Western scholars, show how myths appear in various socio-religious activities of the society. Myths are also considered have moral values for the society that believes in them. The existence of myths in Bantenese society has influenced, more or less, the socio-religious life of the Bantenese. Myths, in some cases, also play significant roles and functions for Bantenese society such as strengthening something, maintaing cultural identity and solidarity of the society, and keeping prestige and social status. Key-words: myth, cultural meaning, Banten